ChemInform Abstract: Synthesis of Substituted 4‐(1H‐Indol‐6‐yl)‐1H‐indazoles as Potential PDK1 Inhibitors. Issue 27 (8th July 2014) - Brzozowski, Martin; O'Brien, Nathan J.; Wilson, David J.D.; Abbott, Belinda M.
Abstract The synthesis of the title compounds (V) is based on the late‐stage Suzuki cross‐coupling of N‐unprotected indazoles with indoles.